2009
DOI: 10.1111/j.1600-6143.2009.02604.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Factors Affecting Health-Related Quality of Life in Adolescents After Liver Transplantation

Abstract: The aim of the study was to identify factors affecting health-related quality of life (HRQL) in adolescents after liver transplantation. HRQL was measured using the CHQ-CF87 in 55 adolescents, aged 12-18 years. Factors associated with HRQL included allograft morbidity, psychological and family-related variables measured through standardized questionnaires. The domains of the CHQ-CF87 were reduced using factor analysis to give physical, psychological and social domains. Impacting factors were identified through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 57 publications
3
74
1
6
Order By: Relevance
“…In their comments the participants referred to areas of life that are not captured by generic QoL instruments, e.g., relationships, bullying, treatment adherence. Also, although differences were noted according to stage of adolescence, this is not apparent using quantitative methods (Taylor et al, 2009), indicating a lack of responsiveness on the part of the QoL instruments. This suggests that currently available PROMs might not be suitable for use with young people after liver transplantation.…”
Section: Implications For Practicementioning
confidence: 90%
“…In their comments the participants referred to areas of life that are not captured by generic QoL instruments, e.g., relationships, bullying, treatment adherence. Also, although differences were noted according to stage of adolescence, this is not apparent using quantitative methods (Taylor et al, 2009), indicating a lack of responsiveness on the part of the QoL instruments. This suggests that currently available PROMs might not be suitable for use with young people after liver transplantation.…”
Section: Implications For Practicementioning
confidence: 90%
“…However, they had similar QOL when compared with other children and adolescents with different chronic illnesses. A follow-up study from the same group focused on adolescents and found them to have significantly lower QOL (self-reported) across multiple domains, similar to adolescents with other chronic illnesses 10. Further, the authors proposed that the necessity of lifelong immunosuppression directly or indirectly may in part be responsible for the reduced QOL.…”
Section: Long-term Outcome: Qolmentioning
confidence: 95%
“…Twenty-two percent of them reported a history of emotional difficulties. When the data were assessed by regression analysis, the factors associated with quality of life were age at transplantation, secondary illnesses, symptom distress, headaches, history of emotional difficulties, self-esteem, and family conflicts [72]. It therefore seems that we should look at numerous factors in adolescents, such as the presence of other diseases and medical complications due to immunosuppression, as well as assessing family relations before and after liver transplantation.…”
Section: Quality Of Lifementioning
confidence: 99%